Land grabbing within a protected area: The experience of local communities with conservation and forestry activities in Los Esteros del Iberá, Argentina. (November 2018) - Busscher, Nienke; Parra, Constanza; Vanclay, Frank
Highlights: Protected areas are not immune from land grabbing. The distinction between land grabbing and green grabbing is increasingly blurred. Social issues are not properly considered in conservation initiatives. From the positioning of local people, conservation is extractivism. Neoliberal conservation is transforming the governance of protected areas. Abstract: Protected areas are increasingly being created, managed and owned by private actors, resulting in land grabs that are often at the expense of local control, livelihoods and biodiversity. Changes in land ownership and land use lead to new governance arrangements, which are full of paradoxes, alter ownership responsibilities, and create clashes of perspectives over how nature should be valued and utilised. Conversely, the presence of new actors potentially also brings about socio-environmental awareness and can open-up arenas for dialogue and multi-level collaboration. Using qualitative research methods, we considered two case studies in the protected area, Los Esteros del Iberá, in the north-east of Argentina: the Harvard Management Company's investments in industrial tree plantations; and the conservation project of Douglas Tompkins (i.e. the Conservation Land Trust). Their activities have increased the complexity of socio-political dynamics in the region, leading to contradictions and conflicts, as well as to a strengthened commitment to manage the Iberá region better. Nevertheless, local communities perceived little difference between green grabbing and land grabbing, with all land transfers increasing inequality.